Assessing the impact of HYV maize in resettlement areas of Zimbabwe - Bourdillon, Michael; Hebinck, Paul; Hoddinott, John F.; Kinsey, Bill; Marondo, John; Mudege, Netsayi; Owens, Trudy (International Food Policy Research Institute, 2007)
High-yield varieties of maize have been widely adopted in Zimbabwe. Although germplasm from the Consultative Group on International Agricultural Research (CGIAR) system has been used in the development of hybrid maize varieties since Zimbabwe's independence, research and dissemination activities involved several organizations in both the public and private sectors. Further, even though adoption of earlier hybrids was widespread—in 1985, more than 85 percent of smallholder maize area was planted with hybrid maize and production doubled over the period 1979-85—rural poverty and child malnutrition remain endemic. Some observers argue that the gains from these hybrids have been concentrated in a few agroclimatic areas and that there has been little impact on child nutritional status. This argument has implications for policy debates not only about raising nutritional status within Zimbabwe but also for the CGIAR system, given its mandate to link improvements in agricultural technology to better nutrition.